Penser le monde d'après Témoigner d'un engagement. Enquêtes dans le Doubs d'étudiantes en sociologie - Laffort, Bruno (Pratiques & techniques, 2023)
This collective work, produced by first-year sociology students under the direction of Bruno Laffort, is the result of surveys conducted during the year 2019-20, i.e. before, during and after the first confinement. Here we find citizens who continue to be interested in 'public affairs', in other, more concrete forms. These commitments are also part of more individualistic societies where the collective, not necessarily present at the beginning, can always emerge. Finally, these people are making another bet: to start by changing things at their own level, by making their practices exemplary. The cases presented in this book do not claim to be exhaustive, but rather to contribute to the reflection on what the "world after" could be.